2013
DOI: 10.1136/annrheumdis-2012-eular.1239
|View full text |Cite
|
Sign up to set email alerts
|

AB1243 Comparison of the sensitivity and specificity of ACCP and anti MCV in rhematoid artheritis patients

Abstract: Background Rheumatoid arthritis is a systemic inflammatory disease that mainly affects small joints. It has a destructive potential, then early diagnosis and treatment can prevent deformities and extra articular manifestations. According to the studies ACCP test is the most sensitive and specific biological marker of the disease, but in some studies Anti MCV is comparable with ACCP as a specific marker. Objectives In this study we compared the sensitivity and specificity of the above mentioned tests. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, they proposed the use of both assays in the initial screening of RA [78]. According to an Iranian study, when taken in isolation, the anti-MCV tests have sensitivity and specificity similar to those of anti-CCP and therefore have no value [79]. Other studies have shown that sensitivity and specificity of anti-MCV are lower than those of anti-CCP [80] [81] [82].…”
Section: Auto-antibodies Against Cyclic Citrullinated Peptide Antibodiesmentioning
confidence: 99%
“…Therefore, they proposed the use of both assays in the initial screening of RA [78]. According to an Iranian study, when taken in isolation, the anti-MCV tests have sensitivity and specificity similar to those of anti-CCP and therefore have no value [79]. Other studies have shown that sensitivity and specificity of anti-MCV are lower than those of anti-CCP [80] [81] [82].…”
Section: Auto-antibodies Against Cyclic Citrullinated Peptide Antibodiesmentioning
confidence: 99%